2019
DOI: 10.1021/acssuschemeng.9b05092
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linked Cellulose Membranes with Robust Mechanical Property, Self-Adaptive Breathability, and Excellent Biocompatibility

Abstract: High-performance breathable bio-based membranes have attracted considerable attention worldwide due to the limited fossil energy resources and the demand for sustainable development.As the most abundant polysaccharide, cellulose is an almost inexhaustible raw material with hydrophilicity, biocompatibility, biodegradability, chemical modifying capacity, etc. that has demonstrated versatile applications. Herein, cellulose membranes (CEMs) with mechanically strong property, self-adaptive breathability, and excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 50 publications
(56 reference statements)
3
24
0
Order By: Relevance
“…6b), in which NIH-3T3 cells was live-dead stained with the green color standing for live cells and the red color standing for dead cells. It's shown that there are no obvious dead cells in both CL-N series lms group and control groups, the cell number all had a fast increase from 1d to 3d incubation and the morphology are all similar broblast-like, indicating that cells could be alive and continuously grew with good cell adhesion in the existence of CL-N series lms, con rming the good biocompatibility of the cellulose lms prepared by NMMO, which is consistent with the chemical crosslinked cellulose lm (Shi et al, 2019). Therefore, it's providing experimental support for potential application of cellulose in food preservation and textiles eld.…”
Section: Discussion and Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…6b), in which NIH-3T3 cells was live-dead stained with the green color standing for live cells and the red color standing for dead cells. It's shown that there are no obvious dead cells in both CL-N series lms group and control groups, the cell number all had a fast increase from 1d to 3d incubation and the morphology are all similar broblast-like, indicating that cells could be alive and continuously grew with good cell adhesion in the existence of CL-N series lms, con rming the good biocompatibility of the cellulose lms prepared by NMMO, which is consistent with the chemical crosslinked cellulose lm (Shi et al, 2019). Therefore, it's providing experimental support for potential application of cellulose in food preservation and textiles eld.…”
Section: Discussion and Resultssupporting
confidence: 70%
“…With the increase of NMMO content from 0-10%, the tensile strength of the cellulose lm increased from 106.1MPa to 149.5MPa, higher than the regeneration cellulose lm fabricated in alkali/urea system (Fig. 4d, Table 1) (Shi et al, 2019). This is because the cellulose lm was prepared with different concentrations of the coagulation bath results in different degrees of crystallinity (Fig.…”
Section: Discussion and Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…This membrane possesses a stable WVT, that is, the WVT would not reduce owing to micropore clogging during usage. [ 119 ] Typical films of this type are hydrophilic polyester and PU films. Introducing hydrophilic groups, such as, amino, hydroxyl, ether, and carboxyl groups, can improve the hydrophilicity of the molecular chain to achieve moisture permeability of the membranes.…”
Section: Various Applications Of Fibrous Membranementioning
confidence: 99%
“…Based on chemical crosslinking to offer the materials good elasticity and toughness, Hu and co‐workers fabricated chemically crosslinked cellulose membranes from NaOH/urea aqueous solution by crosslinking with ECH. [ 91 ] The obtained cellulose membranes exhibited strong mechanical properties with breaking strength of 137.4 MPa and elongation at break of 18.3%, respectively. The membranes displayed self‐adaptive breathability and excellent biocompatibility, showing promising application for biomedical bandages and smart apparel.…”
Section: Regenerated Robust Cellulose Materialsmentioning
confidence: 99%